Effects of copper content on the microstructure and properties of AlCuxCrTiV high-entropy alloys - Ke Liu; Zhaoyang Wang; Lizhong Su; Yuanyuan Chen; Huichen Yu (Journal of Materials Research and Technology)
This study investigates the influence of Cu content on the microstructure and properties of AlCuxCrTiV (x = 0.4, 1.0, 1.7) high-entropy alloys (HEAs) fabricated via vacuum arc melting. Advanced characterization techniques were used to analyze the alloy's composition, microstructure, mechanical performance, and corrosion resistance. The results show that the alloys primarily consist of BCC, FCC, and HCP phases. With increasing Cu content, the HCP phase volume fraction increases, while grain size decreases. Mechanical testing reveals a slight reduction in hardness but significant improvements in strength and fracture strain. The AlCu1.7CrTiV alloy achieves a compressive strength of 1688 MPa, a yield strength of 1443 MPa, and a fracture strain of 17%. Electrochemical tests demonstrate that higher Cu content reduces corrosion current density, increases corrosion potential, and enhances charge transfer resistance, thereby improving corrosion resistance. Overall, Cu promotes HCP phase formation, optimizes the soft-hard phase balance, and enhances ductility while maintaining high strength. Furthermore, Cu bonding strength significantly impacts corrosion resistance. These findings provide valuable insights for the optimization and practical application of AlCuxCrTiV HEAs.